Incorporation of an anaerobic digestion step in a multistage treatment system for sanitary landfill leachate. (July 2016) - Zayen, Amal; Schories, Gerhard; Sayadi, Sami
Graphical abstract: Highlights: Biological, chemical and physical processes were applied for leachate treatment. Importance of the anaerobic digestion step was evaluated. Lime dose was optimized to obtain the maximum reduction of conductivity. Anaerobic digestion decreased optimum lime dose by 50%. Anaerobic digestion step increased MF and RO fluxes by 35% and 40% respectively. Abstract: A combined process of anaerobic digestion (AD), lime precipitation (P), microfiltration (MF) and reverse osmosis (RO) was developed for the treatment of landfill leachate (LFL). The raw LFL contained high amount of organic matter with an elevated humic acids concentration. During the anaerobic digestion step, the organic loading rate was increased progressively up to 3.3 g COD L −1 d −1 . The upflow anaerobic fixed bed reactor showed a great performance in terms of COD removal efficiency and biogas production. During precipitation experiments, lime dose was optimized to obtain the maximum reduction of conductivity to prevent the fouling of RO membranes. This process was compared to a second one in which the AD step was eliminated. Both treatment plans achieved similar removal efficiencies. However, AD step significantly improved the process by reducing the needed lime dose by 50%. It has also increased MF and RO fluxes by 35% and 40% at a steady state, respectively. The dominant fouling mechanism was cake layer formation during both MF tests. This process seems to be a promising approach for the treatment of LFL and its industrial application should be further investigated.